Productivity, soil fertility and economic viability of fodder tree–crop silvipastoral systems in southern Karnataka, India - M. Harshitha; D. C. Hanumanthappa; A. R. Ravi; Gaddam Sudharshan Redday; Abhishek Godi (Agroforestry Systems, 2026)

First report of DMI and QoI fungicides resistance in Erysiphe necator in the Karnataka state in India - N. Sagar; M. M. Jamadar; M. K. Sunil; T. Sushma; K. N. Pallavi; J. Sneha; C. Harshitha (European Journal of Plant Pathology, 2025)

Fatigue performance and thickness optimization of polyolefin fiber-reinforced M40 concrete for sustainable pavements - J. C Vidyashree; E. K Reshma; M. Harshitha; Gopal Bharamappa Bekkeri; Kiran K. Shetty (Innovative Infrastructure Solutions, 2025)
Concrete pavements are renowned for their ability to handle heavier loads and lower life cycle costs than flexible pavements. Fibers into concrete further enhance its durability by reducing maintenance and rehabilitation costs. This study investigates the fatigue performance of pavement quality concrete (PQC) M40-grade reinforced with polyolefin fibers, focusing on structured fibers (SF) and twisted fibers (TF). Polyolefin fibers were added at varying dosages (0.8, 0.9, and 1.0 kg/m³ for structured fibers and 3, 4, and 5 kg/m³ for twisted fibers), as per IRC: 44 (2017) guidelines. Tests were conducted for compressive, split tensile, flexural strength, and flexural fatigue under different stress levels and loading frequencies. Results revealed that polyolefin fibers significantly improve concrete’s mechanical properties and fatigue resistance. Optimal dosages were identified as 1 kg/m³ for structured fibers and 5 kg/m³ for twisted fibers. The S-N curves demonstrated enhanced durability under cyclic loading conditions. Furthermore, polyolefin fiber reinforcement reduced white topping thickness from 19 cm to 17 cm while maintaining flexural stress within safe limits. This optimization highlights the potential for more durable, cost-effective, and sustainable pavement solutions.

Spatio-temporal tectonic progression in the Dharwar Craton: Insights from volcanic records of Archean greenstone belts - G. Harshitha; Jayant K Yadav; C. Manikyamba; M. Santosh; Li Tang; K.S.V. Subramanyam (Precambrian Research, 2025)

Unlocking the Photoluminescence Potential of Tabebuia Rosea Dyes: A Novel Natural Source of Broadband Visible Spectral Fluorescence for OLED Technologies - R Chaithra; D Harshitha; C G Renuka (Journal of Fluorescence, 2025)

Temperature-Dependent Rotational Dynamics of Non-Polar Solute in Non-Polar Solvents: Influence of Boundary Conditions - Anil Kumar; D. Harshitha; C. G. Renuka (Journal of Fluorescence, 2024)

Geochemistry and depositional environment of fuchsite quartzites from Sargur Group, western Dharwar Craton, India - C. S. Sindhuja; G. Harshitha; C. Manikyamba; K. S. V. Subramanyam (Acta Geochimica, 2024)

Anthocyanins of Delonix Regia Floral Petals: A Novel Approach on Fluorescence Enhancement, Forster Resonance Energy Transfer Mechanism and Photostability Studies for Optoelectronic Applications - D. Harshitha; Anil Kumar; H. M. Mahesh; C. G. Renuka (Journal of Fluorescence, 2024)